ФОРМУВАННЯ ПІДПРИЄМНИЦЬКОЇ КОМПЕТЕНТНОСТІ ВЧИТЕЛІВ ПРИРОДНИЧИХ СПЕЦІАЛЬНОСТЕЙ У СИСТЕМІ ПІСЛЯДИПЛОМНОЇ ПЕДАГОГІЧНОЇ ОСВІТИ - Куриш Наталія Костянтинівна (International Journal of Innovative Technologies in Social Science, 2019)
In the process of reforming the Ukrainian education industry, postgraduate education is task with developing entrepreneurial competence in teachers who will be able to prepare students for later life, self-realization and development, active citizenship, professional careers in market conditions. In the article presents the main priorities of the system of postgraduate pedagogical education for the formation of entrepreneurial competence of teachers of natural sciences, which are to ensure the variability, mobility and flexibility of the educational process. The stages of formation of entrepreneurial competence of teachers of natural sciences in postgraduate education have been elaborated, which include entrance testing, training, self- educational activity and initial testing. In the context of such processes of modernization of the system of postgraduate pedagogical education, it is important to review not only the content, but also the forms, methods and approaches to the organization of training of teachers of natural specialties in relation to the formation of entrepreneurial competence. Such systematic training of teachers is aim at prompt reorientation of their activities and formation of teachers of the future.